Creation of one-parametrical model russia for testa "linear algebra, analytical geometry" - Lidiya A. Muratova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In this article for the "Linear Algebra, Analytical Geometry" test, according to the modern theory of testing (IRT) the one-parametrical Russia model is under construction. Latent parameters act as the studied sizes: level of knowledge of examinees and difficulty of tasks. Thus both parameters, and also their initial values received directly after testing are transferred to a uniform linear scale of logits. At calculation of probability of the correct answer on a task logistic distribution is used. As a result of the executed actions characteristic curves of level of knowledge of examinees, level of difficulty of tasks, the combined histograms of these levels, and also graphics of comparison of experimental data with model Russia are constructed. The preliminary analysis of the received results is carried out.